Pengaruh Variasi Temperatur Tuang Pengecoran Produk Pulley Terhadap Kekerasan, Ketangguhan dan Metalografi Berbahan Baku Aluminium Bekas - Sumpena (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Pratama Mulia Surakarta, 2018)
Pulley is a component product that is widely used in power transfer and rotation systems, such as in milling, machines with electric motor and fuel motor drives. The effect of molten metal pouring temperature needs to be examined so that pulley products are obtained which have mechanical properties in accordance with their usefulness. The purpose of this study was to determine the effect of casting temperature variations on pulley casting products on hardness, toughness and metallography of used aluminum raw materials. The smelting process uses a crucible furnace in the Prokalmasi45 University metal casting laboratory. Sand molds are made of three types for casting with different temperatures, each of the same pouring temperature is made of each of the three sand molds. The pouring of aluminum molten metal is carried out at temperatures of 670oC, 700oC and 730oC. Measurement of the temperature of molten metal casting using an infrared measuring instrument is carried out when the molten metal is ready to be poured into the mold. Hardness testing was carried out by Brinell hardness testing machine, toughness testing with ASTM D256-03 standard Charpy impact testing machine and metallographic observation on each specimen using an optical microscope. The test results show that the influence of pouring temperature on hardness is the highest hardness obtained at 700oC pouring with a hardness value of 77.05 BHN, while the lowest hardness value is obtained at pouring 670oC with a hardness value of 64.02 BHN. Effect of pouring temperature on toughness is the highest toughness value obtained at 670oC pouring at 0.0608 joule / mm2, while the lowest toughness value at 700oC pouring is 0.0438 joule / mm2. The influence of the pouring temperature on the microstructure is pouring 700oC to spread the elements of Fe, Si and Mg evenly, while the pouring at temperatures of 670oC and 730oC has almost the same characteristics, namely elements of Fe and Si compound while the elements Al and Mg are separate compounds.